Changes in Coronary Perfusion after Occlusion of Coronary Arteries in Kawasaki Disease - Kwak, Ji Hee (Yonsei University College of Medicine, 2014)
PURPOSE: Myocardial infarction in children with total occlusion of a coronary artery after Kawasaki disease is rare due to multiple collateral vessels. We aimed to investigate the changes in coronary perfusion associated with coronary artery occlusion after Kawasaki disease. MATERIALS AND METHODS: Eleven patients with coronary artery occlusion after Kawasaki disease were investigated. Serial coronary angiographies after total occlusion of a coronary artery were reviewed and the changes were described in all patients with additive information collected. RESULTS: The median age at the occlusion was 5.9 years old. The interval to occlusion was 6.2±6.9 years. Four left anterior descending coronary artery total occlusions and 10 right coronary artery total occlusions were detected. Immediate coronary artery bypass graft for left anterior descending coronary artery total occlusion made right coronary total occlusion occurred in all except one patient and the intervals thereof were 1 year, 1.8 years, and 4 years. Collaterals to the left coronary artery regressed after recanalization, while new collaterals to the right coronary artery developed. In three, collaterals to the right coronary artery decreased without recanalization without clinical signs. CONCLUSION: The right coronary artery should be followed up carefully because of possible occlusion of new onset or changes in collaterals.